ANALISIS PENYEDIAAN FASILITAS PUBLIK BAGI PENYANDANG DISABILITAS DAN AKSEBILITASNYA DI KABUPATEN MIMIKA - Florence Ela Pentury; Maria Goretti Renjaan; Muh. Sabir (Jurnal Ekonomi dan Bisnis, 2024)
This research aims to find out or see the provision of public facilities for people with disabilities and their accessibility in Mimika Regency. The method used is descriptive method. In this research, the data collection techniques used were observation and interviews. Meanwhile, the data analysis instrument used is source triangulation. The results of this research show that there are no public facilities built by the Government, but at the district court office there is accessibility that supports people with disabilities in carrying out their activities. Mozzes Kilangin Airport is a public facility built by the Command. Mozzes Kilangin Airport is still in the process of building accessibility that supports people with disabilities.